Pengaruh Pengembangan Kurikulum Pendidikan Agama Islam Terhadap Prestasi Belajar Mata Pelajaran Pendidikan Agama Islam Siswa SMA Tunas Luhur Paiton Probolinggo - M. Inzah (LP3M Universitas Islam Zainul Hasan Genggong, 2018)
The Effect of Islamic Education Curriculum Development on the Achievement of Learning Subject of Islamic Religious Education High School Student Tunas Luhur Paiton Probolinggo, This research is a quantitative research with descriptive analysis approach and simple regression analysis to 20 randomly selected sample people. Curriculum development data obtained from the accumulation of some test scores held by TPQ SMATL.Pengembangankurikulum Islamic education and learning achievement subjects PAI SMATL students have a strong or significant relationship with the value of r calculated results (0.681) larger than rtabel (0.444 ) at a significance level of 5%. Result of regression analysis obtained conclusion that curriculum development give positive influence to learning achievement of PAI, marked by slope value (slope) positive regression line equal to 0,690. The regression equation obtained (Y = 35,558 + 0,690X) can also explain the diversity of student achievement score significantly based on the result of further analysis with F-value test (15,548) bigger than Ftabel (4,41) at significance level 5 % and with the test of coefficient of determination (r2) value of 0.463. Overall, thus, the proposed hypothesis is accepted, ie that there is a significant (positive) influence of the development of Islamic education curriculum on the achievement of learning subjects PAI high school students Tunas Luhur Paiton Probolinggo. Keywords: Curriculum, Education, Religion, SMA Tunas Luhur